Case report: An illusive cortical venous infarction mimicking glioma hemorrhage - Feng, Dayun; Zou, Le; Qin, Huaizhou; Cai, Qing (Frontiers in Neuroscience, 2022)
Cortical vein thrombosis (CVT) is a rare subtype of cerebral venous and venous sinus thrombosis. Due to the rarity of CVT and the atypical clinical and imaging findings, the possibility of misdiagnosis of CVT is extremely high. We report a case of cortical venous infarction secondary to cortical venous thrombosis. Because of the rarity and atypical symptoms, We were confused between cortical venous infarction and glioma hemorrhage. Eventually, cortical venous thrombosis was confirmed by pathology combined with imaging